Long-term Assessment of Ozone Nonattainment Changes in South Korea Compared to US, and EU Ozone Guidelines - Kim, Jeonghwan; Lee, Jimin; Han, Jin-Seok; Choi, Jinsoo; Kim, Dai-Gon; Park, Jinsoo; Lee, Gangwoong (Asian journal of atmospheric environment (Online), 2021)
We conducted spatiotemporal assessments of ozone in South Korea from 1990–2020 to evaluate trends and compare changes in compliance based on South Korean, US, and EU standards. Observational data from nationwide air-quality monitoring stations were collected and converted to the maximum daily 8 hr ozone average (MDA8O3). Seasonal ozone variations displayed an overall increase across most of South Korea and a noticeably high rate of 0.86 ppbv/yr in Seoul, with an even higher rate 1.2 ppbv/yr for the fourth-highest MDA8O3. Recent air-quality regulations to reduce NOx emissions have been estimated to weaken NO titration effects, leading to higher ozone levels for VOC-limited urban areas in South Korea while decreasing ozone concentrations elsewhere. In recent years, nearly all monitoring stations have exceeded the South Korean MDA8O3 standard, leading to debate regarding the adequacy of current standards for monitoring changes in nonattainment. Comparison with EU and US standards showed that implementing these could significantly lower nonattainment events due to the easing of target threshold values by either percentile or concentration values. Relative distances in nonattainment percentages between South Korean and other standards indicated that the EU ozone guideline was most suitable for tracing recent ozone changes not apparent when using the South Korean or US standards.